Early detection of speech delay and family factors - Lia Kurniasari; Sri Sunarti (AOSIS, 2019)
Speech delay is one common developmental disorders in children. The purpose of this study was to detect factors that affect speech delay in children aged 48- 72 months. This quantitative research used analytical design with cross sectional approach. 159 children were chosen as samples in this study. Data analysis used chi square test. The results showed that family factors of speech delay with p value of 0.853 and factor of working mothers with p value 0.245. In this study, it can be concluded that there is no relationship between family factors and working mothers with speech delay. Parents need to give stimulation to their children so it will improve their language skills. Stimulation by using various game media will help children to practice communication skills.